2013
DOI: 10.1371/journal.pone.0063995
|View full text |Cite
|
Sign up to set email alerts
|

Fusion versus Nonfusion for Surgically Treated Thoracolumbar Burst Fractures: A Meta-Analysis

Abstract: BackgroundPosterior pedicle screw fixation has become a popular method for treating thoracolumbar burst fractures. However, it remains unclear whether additional fusion could improve clinical and radiological outcomes. This meta-analysis was performed to evaluate the effectiveness of fusion as a supplement to pedicle screw fixation for thoracolumbar burst fractures.Methodology/Principal FindingsMEDLINE, OVID, Springer, and Google Scholar were searched for relevant randomized and quasi-randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 24 publications
2
34
0
2
Order By: Relevance
“…There continues to be considerable controversy regarding the treatment of burst fractures of the thoracolumbar and lumbar spine [2][3][4][5][6][7][8] . Nonoperative treatment for burst fractures without neurologic deficit has been reported to yield good results, although a greater residual kyphotic angle was noted [7][8][9][10][11] . However, greater residual deformity does not correlate with symptoms at the time of follow-up 9 .…”
mentioning
confidence: 99%
“…There continues to be considerable controversy regarding the treatment of burst fractures of the thoracolumbar and lumbar spine [2][3][4][5][6][7][8] . Nonoperative treatment for burst fractures without neurologic deficit has been reported to yield good results, although a greater residual kyphotic angle was noted [7][8][9][10][11] . However, greater residual deformity does not correlate with symptoms at the time of follow-up 9 .…”
mentioning
confidence: 99%
“…Operative time, as well as total blood loss, may decrease. 44 The risk of further destabilization of the spinal column caused by posterolateral decortication as part of the fusion procedure is eliminated. The possibility that the fusion substrate could stimulate the growth of cancer cells is removed.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature concerning fusion versus non-fusion in the treatment of unstable thoracolumbar fractures from up to 2012 by Tian et al showed that the average hardware failure rate was 5%. Pooled estimates failed to show that the fusion group achieved less implant failure when compared to non-fusion (p = 0.28) [38].…”
Section: Functional Outcomesmentioning
confidence: 91%
“…Although the use of allograph in place of autograph eliminates donor site pain and complications, costs are elevated and fusion potential may be negatively affected [39]. The length of surgery is also increased by fusion surgery which increases operative costs and may influence infection rates [38,40].…”
Section: Functional Outcomesmentioning
confidence: 99%
See 1 more Smart Citation